Characterization of Key Metabolic Markers in Hongqujiu Across Different Aging Years Using Metabolomics - Yiyang Cai; Sunan Yan; Simei Huang; Bin Yang; Wenlan Mo; Lishi Xiao; Xiangyou Li; Zhiwei Huang (Journal of Fungi)
Hongqujiu, one of the three principal varieties of yellow wine, is a traditional fermented beverage originating from China that employs Hongqu as the fermentation agent. In this study, an untargeted metabolomics approach based on gas chromatography–mass spectrometry (GC-MS) and liquid chromatography–mass spectrometry (LC-MS) was applied to systematically analyze the volatile compounds (VOCs) and non-volatile compounds (NVCs) in Hongqujiu across different aging years for the first time. The analysis identified a total of 262 VOCs and 2564 NVCs in samples of Hongqujiu aged for six distinct years. Based on metabolic differences, the samples were categorized into two groups: the low-year group (5-year, 6-year) and the high-year group (8-year, 10-year, 15-year, 20-year). Nineteen VOCs (e.g., 4-amino-butyric acid and diethanolamine) and thirty NVCs (e.g., palmitoylethanolamide and erinacine D) were identified as key differential metabolites distinguishing the low-year group from the high-year group. The higher-year group is enriched with a variety of substances with different flavors or biological activities, such as sugar derivatives, amino acids and their complexes, organic acids and their intermediate metabolites, steroids and terpenoid compounds, lipids and their derivatives, nitrogen-containing heterocycles, and aromatic compounds. The accumulation of these substances not only shapes the unique and rich flavor characteristics of aged red rice wine (such as the caramel aroma and umami peptide flavor), but also endows red rice wine with potential health benefits due to the physiological regulatory functions of some active ingredients. This study contributes to a deeper understanding of the composition and dynamic variations in metabolites in Hongqujiu, offering a scientific foundation for identifying aged Hongqujiu and conducting further research to enhance its quality.